2021
DOI: 10.31557/apjcp.2021.22.9.2855
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Crosstalks with DR5 to Sensitize TRAIL Resistance and Stimulate ROS-Mediated Cancer Apoptosis

Abstract: Human breast cancer MCF-7 and MDA-MB-231 cell lines provide suitable models for in vitro treatment of breast cancer. Ovarian estrogens are required for the onset and progression of human breast cancer. The MCF-7 breast cancer cell line possesses efficient oestrogen receptors (ER), but the MDA-MB-231 human breast cancer cell line lacks ER and is unresponsive to ER and anti-ER (Ren et al., 2018).There are numerous community therapies for various malignancies that prevent cancer proliferation by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…could be modulated by S. marianum essential oils alone or in combination with 5-FU in H22 cells. Some studies have shown the ability of silymarin to increase apoptosis in various cancers, including gastric cancer cells(Abd-Rabou, Abdalla, Ali, & Zoheir, 2017;Kauntz, Bousserouel, Gosse, Marescaux, & Raul, 2012).In conclusion, our study showed that S. marianum essential oils alone and in combination with 5-FU were able to modulate several HCC-associated cellular pathways, including NF-κB, angiogenesis, autophagy, and apoptosis both in vitro and in vivo. Therefore, that the addition of S. marianum essential oil may improve the effects of firstline anticancer drugs that is, 5-FU against HCC.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…could be modulated by S. marianum essential oils alone or in combination with 5-FU in H22 cells. Some studies have shown the ability of silymarin to increase apoptosis in various cancers, including gastric cancer cells(Abd-Rabou, Abdalla, Ali, & Zoheir, 2017;Kauntz, Bousserouel, Gosse, Marescaux, & Raul, 2012).In conclusion, our study showed that S. marianum essential oils alone and in combination with 5-FU were able to modulate several HCC-associated cellular pathways, including NF-κB, angiogenesis, autophagy, and apoptosis both in vitro and in vivo. Therefore, that the addition of S. marianum essential oil may improve the effects of firstline anticancer drugs that is, 5-FU against HCC.…”
supporting
confidence: 55%
“…Our results showed that the expression of some apoptosis‐associated proteins that is, Caspase 8, Bax, and Bcl‐2 could be modulated by S. marianum essential oils alone or in combination with 5‐FU in H22 cells. Some studies have shown the ability of silymarin to increase apoptosis in various cancers, including gastric cancer cells (Abd‐Rabou, Abdalla, Ali, & Zoheir, 2017; Kauntz, Bousserouel, Gosse, Marescaux, & Raul, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…M. oleifera extract inhibited the increase in mRNA and protein levels of interleukin-6, tumor necrosis factor-alpha, inducible nitric oxide synthase, and cyclooxygenease-2 (Muangnoi et al, 2012). In addition, M. oleifera was able to increase the expression of p53, p21, and Bax which are known as tumor suppressors (Abd-Rabou et al, 2017). The suppressive effect of M. oleifera was also mediated by inhibiting the phosphorylation of the kappa B inhibitor protein (Cirmi et al, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…The cytotoxicity potential of MO extract was studied in HepG2 and MDCK cells using MTT test by adopting the procedure from Barhoi D 21 and Abd Rabou AA. 22 HepG2 and MDCK cells were cultured in a complete medium containing RPMI, 10% Fetal Bovine Serum, 1% of penicillin streptomycin, 1% amphotericin B in a 5% CO 2 incubator. Brie y, 10000 cells of HepG2 or MDCK were grown in a 96 well plates, and were treated with various concentrations of MO extracts (from 3.0 to 500 µg/mL) for 24hours.…”
Section: Phytochemical Analysismentioning
confidence: 99%